The Role of Religious Coping in Understanding the Suicide Risk of Older Adults during COVID-19 - Pulgar, Camila A. (Religions, 2022)
In the United States, racially diverse, homebound older adults have been among those most impacted by the COVID-19 pandemic. During times of disaster, persons impacted tend to turn to their faith to make sense of suffering. COVID-19 has been an unusual disaster, as physical distancing was required to keep those most susceptible safe. Due to the resulting social isolation and loneliness, suicidal behaviors and ideation (e.g., desire to die) have increased during the pandemic. Suicide desire is encapsulated by two states: thwarted belongingness (T.B., chronic loneliness and lack of reciprocal care) and perceived burdensomeness (P.B., belief that one is a burden to others and society) and has historically been inversely correlated with religiosity. Therefore, understanding how religious coping can contribute to the relationship between the impact of COVID-19 on T.B. and P.B. in homebound older adults is important in understanding their suicide risk. Our participants (ages 62–101) varied in suicidality. Increases in suicide desire over time were associated with higher levels of negative religious coping. Implications for treatment are provided, particularly the importance of fostering belongingness, buffering perceived burdensomeness with older adults, and promoting positive religious coping and support. Suggestions for future research are also provided.